PROSPEK KAWASAN WISATA ALAM BERKELANJUTAN GUA GRUBUG DAN GUA JOMBLANG DI PADUKUHAN JETIS WETAN DESA PACAREJO KECAMATAN SEMANU KABUPATEN GUNUNGKIDUL - , BARON BANAL ISLAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ecotourism development in Indonesia is progressing quite fast and could compete with ecotourism development in other countries. Gunungkidul Regency is part of Gunung Sewu Karst area and have potential caves for ecotourism. However, such tourism area has experience in descent quality of environment that lead to social, economy and ecology problems. The main purpose of this research is to evaluate the prospect of sustainable tourism of Grubug and Jomblang Cave. This research used deductive qualitative method. Data collections were done by observation method, spread questionnaire and deep interviews. Sample was taken by purposive sampling. This research found that the development of Grubug and Jomblang Cave progress is very good. Interesting attractions and comfortable facility became main factor of development in this area. Stakeholdersâs perception of tourist agent about the area is very good. Most of respondents felt satisfaction visiting this area. Further, this research argues that the development of Jomblang and Grubug Cave area have fulfilled the principle of sustainable tourism development.It proven to be success to increase prosperity of common and society live in harmony and help each other. The prospect of Jomblang and Grubug Cave karst area as sustainable tourism is very good so long as all of stakeholders keep doing anticipation handling problems which will appear the local government has to be careful in giving permit for mining activities in this area. Keywords: Cave, Special Interest Tourism, Prospect, Sustainable Tourism